Project-Based Learning (PjBL)-STEM: Bibliometric Analysis and Research Trends (2016-2020) - Maharani Ayu Nurdiana Putri; Erina Krisnaningsih; Nadi Suprapro; Utama Alan Deta; Dwikoranto Dwikoranto (Berkala Ilmiah Pendidikan Fisika, 2021)
This study aims to analyze research trends related to PjBL-STEM topics in 2016-2020 through bibliometric analysis with the Scopus database. Based on the criteria, it obtained 1,169 documents. Microsoft Excel was used to analyze data and VOS viewer as a data visualization. The results showed that PjBL-STEM research is increasing every year. The USA contributes the most research in the world, Indonesia ranks second. Universitas Pendidikan Indonesia, Universitas Negeri Malang, Universitas Sebelas Maret, and Universitas Negeri Semarang are among the top affiliates in PjBL-STEM research in the world. Visualizing the trend of PjBL-STEM research in 2016-2020, there are three clusters, namely 1.) PjBL-STEM as a framework, 2.) PjBL-STEM as self-development, and 3.) Effects of PjBL-STEM research. The results of this study can help researchers related to PjBL-STEM research trends in the world and provide direction in further research.